Hydraulic Structure as a Solution to Flooding in the Santa Bárbara de Carhuacayan District, Junín. - Roca Bonifacio, Gerardo Enrique (2024)
In Peru, many populations are established near rivers to take advantage of water resources, which carries risks of flooding and erosion, especially during periods of high river flow. The Carhuacayan River, affected by heavy rainfall between December and March, generates debris that is carried to its banks, causing undermining and siltation that threaten the stability of inhabited areas. The aim of this study was to determine the hydraulic and geomorphological parameters needed to design riverbank defenses to mitigate these risks. The geological and hydrological characteristics of the area were analyzed, and scouring was calculated using numerical and empirical methods. Based on this data, structures such as gabion walls and dikes were designed and modeled. Among the results, vulnerable areas were identified, morphometric parameters were calculated, the design flow rate and scour profile were determined, and the optimal dimensions for the protection structures were defined. Additionally, an environmental impact assessment was conducted, and a project budget was developed. It was concluded that the construction of riverbank defenses in flood-prone areas will effectively mitigate the risks of overflow and flooding, ensuring the stability and safety of human settlements. This comprehensive approach combines protection against natural events with environmental sustainability and economic feasibility.